Adversıty Quotıent: Perspectıves On Work Challenges For Mıllennıals And Beyond - Nia Kusuma Wardhani; Windu Gata (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study examines the Adversity Quotient (AQ) among millennial employees in Indonesia, focusing on the dimensions of Control, Ownership, Reach, and Endurance (CORE). Using a qualitative approach, the study integrates text mining methods to analyze responses from millennial and Generation Z employees. The findings indicate that AQ plays a crucial role in helping employees effectively handle work challenges through the development of critical thinking, resilience, and adaptability. Employees with high AQ tend to perform better and adapt to the dynamic changes in the workplace environment. This research provides insights for managers and stake holders to develop strategies that support AQ development in employees, particularly in today’s competitive and digital era